Efecto del clima sobre la respuesta térmica en vacas de diferentes grupos raciales en trópico bajo - Molina-Benavides, Raúl Andrés; Perilla-Duque, Sandra; Campos-Gaona, Rómulo; Sánchez-Guerrero, Hugo; Rivera-Palacio, Juan Camilo; Muñoz-Borja, Luis Armando; Jiménez-Rodas, Daniel (University of Cordoba, 2023)
Objective. The main idea of this study was to quantify the relationship between climatic variables and tympanic body temperature recorded through the use of wireless sensors in grazing cows located in low tropic. Material and methods. The tympanic temperature of twenty-eight cross breed grazing cows in early lactation was monitored. The sensors were manually installed in the tympanic cavity, recording hourly for 17 days. The climate data was obtained from the network of weather stations of the Centro de Investigación de la Caña de Azúcar “Cenicaña”, which is a research center for sugarcane located in Cali, Colombia, this data was analyzed for the same time interval of the temperature. The information was analyzed using descriptive statistics, correlation matrices and Random Forest models, through the R software. Results. From the physiological data from automatic collection systems, the response variables that would allow the evaluation of thermoregulation processes were analyzed using big data. We find that the variables environmental temperature, relative humidity and, solar radiation were the factors that most influenced the homeothermic adaptation process of the animals. Conclusions. The introduction of remote devices, and the use of a large amount of data for the analysis of physiological indicators, avoid modifying natural animal behavior and emerges as an important diagnostic and management strategy in the livestock farm, helping in the studies of heat stress, physiological adaptation and, prevalence to hemotropic diseases, which reduce the productivity of the systems.